Key factors for effective implementation of healthcare workers support interventions after patient safety incidents in health organisations: a scoping review - Helena Donato; José Joaquín Mira; Irene Carrillo; Paulo Sousa; Sofia Guerra-Paiva; Maria João Lobão; Diogo Godinho Simões; Joana Fernandes (BMJ Open)
Objectives This study aims to map and frame the main factors present in support interventions successfully implemented in health organisations in order to provide timely and adequate response to healthcare workers (HCWs) after patient safety incidents (PSIs).Design Scoping review guided by the six-stage approach proposed by Arksey and O’Malley and by PRISMA-ScR.Data sources CINAHL, Cochrane Library, Embase, Epistemonikos, PsycINFO, PubMed, SciELO Citation Index, Scopus, Web of Science Core Collection, reference lists of the eligible articles, websites and a consultation group.Eligibility criteria for selecting studies Empirical studies (original articles) were prioritised. We used the Mixed Methods Appraisal Tool Version 2018 to conduct a quality assessment of the eligible studies.Data extraction and synthesis A total of 9766 records were retrieved (last update in November 2022). We assessed 156 articles for eligibility in the full-text screening. Of these, 29 articles met the eligibility criteria. The articles were independently screened by two authors. In the case of disagreement, a third author was involved. The collected data were organised according to the Organisational factors, People, Environment, Recommendations from other Audies, Attributes of the support interventions. We used EndNote to import articles from the databases and Rayyan to support the screening of titles and abstracts.Results The existence of an organisational culture based on principles of trust and non-judgement, multidisciplinary action, leadership engagement and strong dissemination of the support programmes’ were crucial factors for their effective implementation. Training should be provided for peer supporters and leaders to facilitate the response to HCWs’ needs. Regular communication among the implementation team, allocation of protected time, funding and continuous monitoring are useful elements to the sustainability of the programmes.Conclusion HCWs’ well-being depends on an adequate implementation of a complex group of interrelated factors to support them after PSIs.